Study on the Shielding Effectiveness of an Arc Thermal Metal Spraying Method against an Electromagnetic Pulse - Lee, H.-S.; Choe, H.-B.; Baek, I.Y.; Singh, J.K.; Ismail, Mohamed (mdpi, 2017)
An electromagnetic pulse (EMP) explodes in real-time and causes critical damage within a short period to not only electric devices, but also to national infrastructures. In terms of EMP shielding rooms, metal plate has been used due to its excellent shielding effectiveness (SE). However, it has difficulties in manufacturing, as the fabrication of welded parts of metal plates and the cost of construction are non-economical. The objective of this study is to examine the applicability of the arc thermal metal spraying (ATMS) method as a new EMP shielding method to replace metal plate. The experimental parameters, metal types (Cu, Zn-Al), and coating thickness (100–700 μm) used for the ATMS method were considered. As an experiment, a SE test against an EMP in the range of 103 to 1010 Hz was conducted. Results showed that the ATMS coating with Zn-Al had similar shielding performance in comparison with metal plate. In conclusion, the ATMS method is judged to have a high possibility of actual application as a new EMP shielding material.